The influence of germline mutations on breast cancer - Fernanda Sperotto Valadares Gontijo, Maria; Lazarino, Luísa; Caroline, Avelar; Apolinário, João Pedro; Henrique, Galvão; Salvador, Anna Dias; de Avelar, José Tadeu Campos (Mastology, 2025)
The ability to evade protection mechanisms and uncontrolled cell growth can lead to the development of mutations, whether somatic or germline, and consequently to the dreaded diagnosis of cancer. Breast cancer is considered the most common type of cancer in women in several regions of Brazil, mainly in the South and Southeast, second only to non-melanoma skin cancer. Approximately 5% to 10% of neoplasms are related to germline alterations that lead to hereditary predisposition. There is evidence of an association with mutations in nine genes, the highest risk being breast cancer 1 (BRCA1) and breast cancer 2 (BRCA2). Due to its epidemiological importance, in this narrative review we observed the main genetic mutations and syndromes associated with breast carcinoma, the recommendations for screening in high-risk patients, and the indication for genetic counseling. Bibliographic research on the PubMed and Cochrane databases and analysis of the Guidelines Breast Cancer Risk Reduction and Breast Cancer Screening and Diagnosis, from June 2022 to September 2023. In this review, we observed a greater influence of germline mutations on breast cancer related to the genes BRCA1, BRCA2, PALB2, PTEN, CDH1, STK11 and, in Brazil, considered a country of ethnic-racial diversity, to TP53. As cancer screening in the country is opportunistic, knowledge of germline mutations associated with breast cancer offers specific screening recommendations for high-risk patients, indications for genetic counseling, and guidelines for prophylactic surgery, in addition to impacting the formulation of public screening policies.